Preparation of methoxy and ethoxy nonafluorobutanes - Hwang, Sun-Hee; Kim, Ju-Ryun; Lee, Sang Deuk; Lee, Hyunjoo; Kim, Hoon Sik; Kim, Honggon (KOREAN SOC INDUSTRIAL ENGINEERING CHEMISTRY, 2007)
Syntheses of methoxynonafluorobutane (C4F9OCH3) and ethoxynonafluorobutane (C4F9OC2H5), which are considered as prospective third generation alternative cleaning agents replacing CFC-113 (CF2ClCFCl2), CH3CCl3, and HCFC-141b (CH3CFCl2), were studied. Heptafluorobutyryl chloride (C3F7COCl) or heptafluorobutyryl fluoride (C3F7COF) was firstly reacted with alkali metal fluoride (KF or CsF) in an aprotic polar solvent to produce alkali metal nonafluorobutoxide. It was consecutively converted to C4F9OCH3 and C4F9OC2H5 through the reaction with alkylating agents such as dimethyl sulfate, methyl trifluoromethane sulfonate and diethyl sulfate. Identification and characterization of major products were carried out by GC-MS, FT-IR, H-1-NMR, and F-19-NMR spectroscopies.
Keywords: FULLY FLUORINATED ALKOXIDES; CHEMISTRY; FLUORIDE